The Transformation of Local Cultural Values in Digital Poetry in the Post-Instagram Era - Sosiana Sosiana (Jurnal Multidisiplin Sahombu, 2026)
This study examines the transformation of local cultural values in digital poetry in the post-Instagram era. The rapid development of digital media has significantly reshaped literary production and distribution, particularly poetry, which has shifted from print-based formats to multimodal digital platforms. In this context, local cultural values are no longer presented solely through textual symbolism but are reconstructed through visual, audio, and performative elements influenced by algorithmic systems and audience engagement patterns. This research employs a qualitative descriptive approach using critical discourse analysis and digital semiotics. The data consist of 50 digital poems published after 2022 across various social media platforms, selected based on their incorporation of Indonesian local cultural elements and significant audience interaction. The analysis focuses on identifying forms of cultural representation, examining patterns of transformation, and interpreting their implications within the digital ecosystem. The findings reveal three primary forms of transformation: symbolic reduction, contextual reinterpretation, and aesthetic commodification. Symbolic reduction occurs when complex cultural meanings are simplified to align with fast-paced digital communication. Contextual reinterpretation reflects the adaptation of traditional values to contemporary issues such as identity and social awareness. Meanwhile, aesthetic commodification emerges when cultural elements are strategically utilized to enhance visual appeal and digital visibility. The study concludes that digital poetry serves as both a space for cultural preservation and a site of negotiation between tradition and digital modernity. While digital platforms expand the reach of local culture, they also risk simplifying its depth due to algorithm-driven visibility and audience preferences. This research contributes to the interdisciplinary study of digital literature, cultural transformation, and media sociology in contemporary Indonesian literary discourse.